2023
DOI: 10.1007/s12672-023-00632-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonconvulsive status epilepticus characteristics in glioma patients: a retrospective study

Abstract: Purpose Epilepsy is a common complication of gliomas. The diagnosis of nonconvulsive status epilepticus (NCSE) is challenging because it causes impaired consciousness and mimics glioma progression. NCSE complication rate in the general brain tumor patient population is approximately 2%. However, there are no reports focusing on NCSE in glioma patient population. This study aimed to reveal the epidemiology and features of NCSE in glioma patients to enable appropriate diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A limited number of studies have focused on this specific patient group, and the majority of these were retrospective, involved only a single center, and consisted of small patient cohorts. Our literature review identified seven original studies [ 14 , 16 , 33 37 ] and two reviews [ 9 , 15 ], the details of which are presented in Table 4 . These studies indicated that SE patients with brain tumors averaged 55–68 years of age and mainly included males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have focused on this specific patient group, and the majority of these were retrospective, involved only a single center, and consisted of small patient cohorts. Our literature review identified seven original studies [ 14 , 16 , 33 37 ] and two reviews [ 9 , 15 ], the details of which are presented in Table 4 . These studies indicated that SE patients with brain tumors averaged 55–68 years of age and mainly included males.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported tumor-associated SE refractoriness ranging from 12 to 57.9% [ 9 , 14 16 , 33 37 ]. Reviews have indicated that TASE tends to be more responsive than SE to first- and second-line ASMs in the general population, with refractoriness evident in only 12–18% of cases [ 9 ].…”
Section: Discussionmentioning
confidence: 99%